Cameriere's third molar maturity index in assessing age of majority. (July 2015) - Galić, Ivan; Lauc, Tomislav; Brkić, Hrvoje; Vodanović, Marin; Galić, Elizabeta; Biazevic, Maria Gabriela Haye; Brakus, Ivan; Badrov, Jozo; Cameriere, Roberto
Highlights: Third molar maturity index ( I 3M ) provide information about development of third molars. Sensitivity and specificity of the 0.08 value for I 3M to discriminate adults from minor are very good. I 3M could be used to discriminate adults from minors. Abstract: Estimation of chronological age of an individual is one of the main challenges in forensic science. Legally to be able to treat a person as a minor or an adult, it is necessary to determine whether their age of majority (if they are older or younger than 18, in most countries). Methods for estimating age are especially important when an individual in question lacks personal documents or other means of identification. As the dental age differs in various populations, the aim of this study was to evaluate applicability of third molar method for assessing age of majority in Croatia. Cameriere's third molar maturity index ( I 3M ) value of 0.08, measured by the open apices of the teeth, was verified in sample of 1336 panoramic images aged between 14 and 23 years. Chronological age gradually decreased as I 3M increased in both genders. Males showed statistically significant advanced maturation when I 3M was between 0.0 and 0.3 value. The results indicate that the sensitivity of the test for 0.08 value was 84.3% (95%CI 80.6%, 87.5%) for females and 91.2% (95%CI 88.7%, 93.1) for males. Specificity was 95.4% (95%CI 92.5%, 97.5%) and 91.9% (95%CI 88.8%, 94.3%). The proportions of accurately classified males were 88.8% and that of females 91.5%. The estimated post-test probabilities, of individuals, in other word the probability that a Croatian individual with an I 3M  < 0.08 is 18 years or older is 94.5% for females, and 96.5% for males. With high accuracy, the third molar maturity index should be used as a determinant of the age of majority in Croatia.